Fire Hotspot and Particulate Matter (Pm2.5) Distribution Patterns In Tropical Rainforest Ecosystems Of Batanghari River Basin In July 2021 - Wibowo, Andrio A; Basukriadi, Adi; Nurdin, Erwin (Universitas Brawijaya, 2022)
Rainforest in the Batanghari River basin is one of the tropical ecosystems that currently is threatened by deforestation, slash and burn swidden farming that lead to the increased numbers of fire hotspots. The fire hotspots are high in midyear during the dry season when a swidden farming activity starts. Then this study aims to assess the distribution of fire hotspots and its impact in the form of PM2.5 contents. The study was conducted in the rainforest of the Batanghari River basin in midyear in July 2021. The methods to classify the rainforest covers and to detect fire hotspots and PM2.5 contents were based on remote sensing and GIS analysis using Landsat 8 OLI, VIIRS, and MODIS remote sensing imageries. The result showed increasing trends of daily fire hotspot numbers in the rainforest of the Batanghari River basin for one month in July 2021. There were significant differences in the daily average of fire hotspots based on the week (P = 0.006, F = 8.677). The daily average of hotspots in the first week of July 2021 was 1.333 hotspots (95%CI: 0-3.94 hotspots). Whereas in the third and fourth weeks, there were sharp increases in the daily average of hotspots. In the third week, the average of hotspots was 4.333 hotspots (95%CI: 0-9.04 hotspots) and increased almost threefold in the fourth week with 11.000 hotspots (95%CI: 7.61-14.4 hotspots). In the areas where the fire hotspots have occurred, the PM2.5 contents ranged from 30 to 80 Î¼g/m3.